Keanekaragaman Coccinellidae Predator pada Ekosistem Pertanian Organik dan Anorganik di Provinsi Sumatera Barat - Siska Efendi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The main principle of pest control in organic farming is to reduce the use of synthetic chemicals, especially pesticides. On the other hand, pest control in agricultural systems prioritizes the conservation of natural enemies in these ecosystems. Coccinellidae predators are one of the potential natural enemies available in organic farming ecosystems. To optimize the potential of these natural enemies, it is necessary to study the diversity of these predators in organic farming. By knowing the species and abundance of Coccinellidae predators in organic farming ecosystems, a suitable conservation model can be designed for these natural enemies so that these predators can carry out their functions to control pests, especially aphids. This study aims to study the diversity of predatory Coccinellidae in organic and inorganic agriculture in West Sumatra Province. Coccinellidae predators are collected directly and use insect nets. The diversity of Coccinellidae predators was analyzed with the Shannon Winner and Simpson abundance indexes. Based on the exploration carried out on several organic farms in West Sumatra, 18 species of Coccinellidae Predators have been collected, and six species have not been identified. Next, it is proven that organic farming has a high diversity of 1.90 compared to inorganic farming, which is 1.65. The presence of predatory Coccinellidae in organic farming is more evenly distributed, namely 0.67. Menochilus sexmaculatus is one species that has the potential to be optimized as a biological control agent for aphids.